"We Will Probably Figure It out Eventually." How Secondary Students Read and Comprehend News Articles About Illiteracy. Issue 1 (2nd January 2023) - Feucht, Florian C.; Michaelson, M. Kate; Ziegler, Nathan E.; Maziarz, Lauren N.; Hany, Susan B.
Abstract: This exploratory qualitative study gathered data on adolescents' mental models of illiteracy before and after they read news articles on the topic and explored their epistemic beliefs about illiteracy and news articles as a knowledge source. Engaging with the news requires critical thinking and civic engagement, both central components of education in a democratic society. In order to investigate how students run and revise their mental models in the face of these demands, researchers provided twelve students from a rural, Midwestern high school with news articles on the topic of illiteracy. Using semi-structured interviews, think-alouds, and hands-on close reading activities, researchers tracked how participants' beliefs on the source and stability of knowledge illustrated their epistemic beliefs about illiteracy, as well as how they established criteria in sorting information across texts. The study found that most participants showed the ability to incorporate better ways of thinking about illiteracy after engaging in a guided reading activity, and some subsequently exhibited changes in their epistemic beliefs on the topic. The findings provide insight into how adolescent learners approach news articles in classroom reading activities and how their epistemic beliefs interact with their engagement.